Internalization of Islamic Values through School Culture in Character Formation of Students at MI AL-Hidayah Kebon IX Sungai Gelam: A Naturalistic Qualitative Study - Ahmad Syukri Saleh; Ahmad Husen Ritonga; Wanada Siti Salsabilah (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to explore the internalization of Islamic values through school culture in shaping students’ character at MI AL-Hidayah Kebon IX Sungai Gelam. Methodology: A qualitative naturalistic approach was employed to capture the authentic experiences and practices within the school environment. research was conducted at MI AL-Hidayah Kebon IX Sungai Gelam. data analysis process followed data reduction, data display, and conclusion. Main Findings: The findings indicate that Islamic values are internalized through a combination of religious routines, habituation practices, teacher role modeling, and a supportive environment, which collectively contribute to the development of students’ character, including religiosity, discipline, responsibility, and respect. Novelty/Originality of this study: The novelty of this study lies in its integrative analysis of Islamic value internalization, school culture, and character formation within a naturalistic framework, highlighting the role of implicit practices and lived experiences in basic education contexts.